PERANCANGAN SISTEM INFORMASI CAPAIAN KINERJA PEGAWAI BERBASIS WEB DI BADAN PUSAT STATISTIK KABUPATEN BANYUWANGI - Sofi Naila Nuriyazih; Zaehol Fatah; Abdul Hadi (CV. Denasya Smart Publisher, 2025)
System design is a series of activities that describes in detail the system being implemented. The design of the information system for the employee performance report at the Central Statistics Agency (BPS) Office of Banyuwangi Regency assists stakeholders in monitoring the performance of employees who are carrying out their work. By creating this system design, the process of monitoring reports becomes easier and more effective. The method used in the system design employs the Software Development Life Cycle (SDLC) method with a prototype model that involves several stages, namely problem identification, needs analysis, system modeling design, and system prototype design. The result of this research is a prototype design in the form of a dashboard that is needed in the system so that each user can input completed work data in real-time and stakeholders can monitor reports from employees. Thus, the design of the employee performance achievement information system at the BPS Office of Banyuwangi Regency can play a role and function to assist in a more structured employee performance administration.